Climate risk and food security in Mali: A historical perspective on adaptation. Issue 2 (2nd February 2017) - Giannini, Alessandra; Krishnamurthy, P. Krishna; Cousin, Rémi; Labidi, Naouar; Choularton, Richard J.
Abstract: We combine socioeconomic data from a large‐scale household survey with historical climate data to map the climate sensitivity of availability and access dimensions of food security in Mali, and infer the ways in which at‐risk communities may have been impacted by persistent climatic shift. Thirty years after 1982–1984, the period of most intense drought during the protracted late 20th century drying of the Sahel, the impact of drought on livelihoods and food security is still recognizable in the Sahelian center of Mali. This impact is expressed in the larger fraction of households in this Sahelian center of the country—the agro‐ecological transition between pastoralism in the north, and sedentary agriculture in the south—who practice agriculture but not livestock raising, despite environmental conditions that are suitable to their combination. These households have lower food security and rely more frequently on detrimental nutrition‐based coping strategies, such as reducing the quantity or quality of meals. In contrast, the more food secure households show a clear tendency toward livelihood diversification away from subsistence agriculture. These households produce less of what they consume, yet spend less on food in proportion. The analysis points to the value of interdisciplinary research—in this case bridging climate science and vulnerability analysis—to gain a dynamical understanding of complex systems, understanding which may be exploited to address real‐world challenges, offering lessons about food security and local adaptation strategies in places among the most vulnerable to climate. Key Points: The effects of multidecadal drought are still felt in the Malian Sahel Livelihood diversification has positive effects on food security Adaptation needs to address an increasingly variable climate, on subseasonal and interannual timescales